CONCRETE REPRESENTATIONAL ABSTRACT APPROACH TO IMPROVE STUDENTS' PROBLEM SOLVING SKILLS ON HEAT MATERIAL - Malik, Adam; El Rachman, Rifelda Fanka; Kuntadi, Dedi (Science Education, Institut Agama Islam Negeri Ponorogo, 2022)
This study aimed to determine the implementation of physics learning with the Concrete Representational Abstract (CRA) approach on the heated material and the improvement of students' problem-solving skills using the CRA approach on the heated material after learning. The population of this research is all class VII in one Madrasah Tsanawiyah in the Majalengka district. the research sample is class VII-B with 20 students. The sample used a simple random sampling determination technique. The research method used is a pre-experimental design with one group pretest-posttest design. The data on the results of the implementation of learning with the CRA approach were obtained using an observation sheet, while the data for improving the problem-solving skill was obtained through an essay test of five questions. The study results for three meetings showed that the activities of teachers and students using the CRA approach had increased, with an average teacher activity of 81.37% in the excellent category and student activities of 77.15% in the excellent category. There is an increase in the student's KPM on heat material with an average N-Gain value of 0.71, which is in the high category. The normality test results showed that the pretest and posttest data were normally distributed, so the t-test was used to test the hypothesis. The results obtained are tcount (25.58) > ttable (1.73), which means Ho is rejected, and Ha is accepted. Thus, the student's problem-solving skill increases using the CRA approach to the heated material.